THE MANAGEMENT OF COOPERATIVE LEARNING ACTIVITIES TO PROMOTE VOLUNTEERISM OF UPPER SECONDARY SCHOOL STUDENTS IN MUNICIPAL SCHOOL 1 (BAN PHO KLANG) UBON RATCHATHANI PROVINCE - sampannamedhi (kongmag), Phra Athikansudthisak; Sukumal, Panjitr (Journal of Buddhist Education and Research (JBER), 2020)
The objectives of this research were: to study the conditions; to compare and to propose the guidelines for the management of cooperative learning activities in promoting volunteerism of upper secondary school students in Municipal School 1 (Ban Pho Klang), Ubon Ratchathani province. The sample groups included 130 students from upper secondary school students in the Municipal School 1 (Ban Pho Klang). The sample size was determined by the Krejcie & Morgan table by simple random sampling. The research instruments were a questionnaire and an interview form. The statistics used in data analysis were: Frequency, Percentage, Standard Deviation, t-test (independent samples) and f-test. The research results were as follows: 1) The conditions of cooperative learning activities in promoting volunteerism of upper secondary school students at Municipal School 1 (Ban Pho Klang), in overall and each aspect were rated at a high level. It was seen in the following respective order of the studied aspects: 1) harmony; 2) generosity; 3) teamwork; 4) responsibility and 5) sacrifice. 2) The comparison of students’ opinions on organizing the cooperative learning activities in promoting volunteerism of upper secondary school students at Municipal School 1 (Ban Pho Klang), classified by gender, educational levels and GPA in all five studied aspects showed the opinions were not significantly different at the level of .05, therefore this rejected the hypothesis. 3) The guidelines for organizing the cooperative learning activities in promoting volunteerism of upper secondary school students at Municipal School 1 (Ban Pho Klang) are that teachers should promote students to have generosity and care for those around them regularly, have the volunteer spirit to work for others without hoping for compensation, to respect and follow the rules and regulations of the school strictly, cooperate and work together in unity; the teachers have ways to promote and support volunteer activities for the clear development of the students according to the set objectives. The results of this research are also in line with the Royal Volunteer Spirit Project in accordance with the royal initiative in order to honor and show gratitude of His Majesty the King Maha Bhumibol Adulyadej, the Great for the benefit of the people. This is for people to have harmony, happiness and sustainable stability of the country.